Building back better: what does it imply for Jiri Technical School, Dolakha, Nepal? (Journal of Training and Development, 2016)
A powerful earthquake of 7.8 magnitude struck on April 25, 2015 in Nepal. The impact was most severe where 8,790 casualties and 23,300 injured (National Planning Commission [NPC], 2015). Due to earthquake there was huge loss in education sector. In TVET sector Jiri Technical School, Dolakha, Nepal faced huge loss where almost all classroom including workshops, labs, hostel and cafeteria were damage. So, this study tries to portray the understanding perception of Jiri Technical School students on impact of earthquake on education and also educational resilience by using case study research design.